Strategi Kreatif Content Creator Potensi Utama Dalam Memproduksi Video Obrolan Bisnis Dan Kewirausahaan (Obkan) - Triadi Sya’dian; Muhammad Ali Mursid Alfathoni; Rinanda Purba; Giovani Giovani; Yoanda Paimin (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2022)
With the development of digital technology, people can easily access various types of information. The information on various social media platforms is certainly packaged with a creative process. To package this information, an agency needs a team known as content creators. The object of this study is the video Obrolan Bisnis dan Kewirausahaan (OBKAN) produced by the Main Potential content creator team. The research method used is qualitative with a case study approach. These methods and approaches are quite relevant in describing the stages of creative strategies used by the Main Potential content creator team. The results showed that the creative strategies used consisted of determining themes and ideas, target audiences, script language and event formats, and the use of gimmicks. In addition, it also refers to production operational standards consisting of pre-production, production, and post-production. This research is considered important to do because in today's digital world, many creative people are born who create various types of content. When producing content, of course, it has a series of creative stages.